Study of reduction of antioxidant protection in the pathogenesis of experimental diabetic retinopathy - Ya. V. Sirman; N. I. Preys; I. V. Savytskyi (Kazimierz Wielki University, 2020)
The prevalence of diabetes mellitus (DM) is growing among the population of countries of the world, depending on the region, the level of economic development of the country, gender and age. The antioxidant system plays an important role in protecting the cells of the body from permanent and numerous damage that occurs due to the pathological influence of free radicals. Antioxidant enzymes, and peroxidases in particular, block the initiation of chain oxidation processes, preventing, among other things, the processes of DNA damage by free radicals that provoke the process of mutagenesis. Our results indicate the development of oxidative stress in the pathogenesis of experimental diabetic retinopathy, as evidenced by a pronounced decrease in the activity of the antioxidant defense enzyme under the conditions of our study. Already on the thirtieth day of the development of experimental diabetic retinopathy, a decrease in peroxidase activity was observed, followed by the progression of pathological changes on the sixtieth day of the study. The most pronounced decrease in the activity of the studied marker of antioxidant defense was found at the 3rd stage of the experiment.